2017
DOI: 10.1371/journal.pone.0172739
|View full text |Cite
|
Sign up to set email alerts
|

How components of facial width to height ratio differently contribute to the perception of social traits

Abstract: Facial width to height ratio (fWHR) is a morphological cue that correlates with sexual dimorphism and social traits. Currently, it is unclear how vertical and horizontal components of fWHR, distinctly capture faces’ social information. Using a new methodology, we orthogonally manipulated the upper facial height and the bizygomatic width to test their selective effect in the formation of impressions. Subjects (n = 90) saw pair of faces and had to select the face expressing better different social traits (trustw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 32 publications
3
28
0
1
Order By: Relevance
“…In humans, FWHR–the ratio between upper facial height and the bizygomatic width - is used implicitly to form social judgements from facial appearance such as trustworthiness 12 and dominance 49 , 50 , and we recently showed that the upper facial height is a robust predictor of trust 51 .…”
Section: Resultsmentioning
confidence: 99%
“…In humans, FWHR–the ratio between upper facial height and the bizygomatic width - is used implicitly to form social judgements from facial appearance such as trustworthiness 12 and dominance 49 , 50 , and we recently showed that the upper facial height is a robust predictor of trust 51 .…”
Section: Resultsmentioning
confidence: 99%
“…The authors further suggested the measurement of additional points, ratios, and distances to keep the research from over-focusing on the same subset of indicators with inconsistent results [19]. Moreover, the authors of a study suggested the facial height and width should be tested independently to reduce the ambiguity of using the ratio between these two components [8]. In another study, the authors discussed that the missing link causing inconsistent results between fWHR and aggression could be the lack of control over critical influencing factors such as BMI [25].…”
Section: Discussionmentioning
confidence: 99%
“…It will be necessary to assess the extent to which fWHR and its interaction with income map onto other trait and behavioral outcomes in women. Furthermore, as a recent study showed that the effect of the vertical component of fWHR plays a different role during the formation of social impressions compared to the horizontal component [ 65 ]; future research may further investigate the single components of the fWHR and their specific relationship with personality traits. It would also be interesting to compare the different effects of objective and subjective social status on the relationship between fWHR and outcomes of social dominance.…”
Section: Discussionmentioning
confidence: 99%